Czech education in nature traditions. Issue 1 (6th April 2020) - Martin, Andrew; Watson, Geoff; Neuman, Jan; Turčová, Ivana; Kalkusová, Lucie
Abstract : Purpose: The purpose of this paper is to examine Czech traditions of outdoor games and sports, turistika activities and education in nature programmes, which have continued to develop during periods of oppression and provided opportunities to preserve the Czech culture. Design/methodology/approach: A review of the historical, cultural and political context of education in nature traditions in Czech was proposed. Findings: Late 19th century organisations such as the Turistický klub and Sokol were instrumental in developing a range of indigenous turistika activities involving active movement. The early 20th century influences were the Czech scouting movement, summer camps and Woodcraft. Charles University provided the first tertiary outdoor educational programmes in Prague in the 1950s. Their foundation course "Turistika and Outdoor Sports" is still compulsory for all students studying physical education and sport. Turistika activities and outdoor sports and games continued to be developed throughout the liberalization of the socialist regime in the 1960s. Practical implications: Following the Prague Spring in 1968, and under the guise of the Socialist Youth Union organization, new experimental forms of outdoor education emerged. Social implications: Since the Velvet Revolution in 1989 organisations have reconnected with Czech outdoor traditions that flourished before 1948 and other organisations have developed education in nature programs. The commercial sphere, which did not exist before 1989, has now been established in the outdoor area. However, traditional participation in turistika activities has been impacted by other external motivations as a broader range of opportunities have become available and accepted, and tourism outside of Czech and Europe has become increasingly popular and accessible. Originality/value: The originality of this paper is to provide an overview of Czech political and cultural history and how it has shaped people's relationship, particularly children and youth, with the outdoors.